Tight Junction Proteins as Therapeutic Targets to Treat Liver Fibrosis and Hepatocellular Carcinoma - Saviano, Antonio; Roehlen, Natascha; Baumert, Thomas F. (Seminars in Liver Disease, 2024)
In the last decade tight junction proteins exposed at the surface of liver or cancer cells have been uncovered as mediators of liver disease biology: Claudin-1 and Occludin are host factors for hepatitis C virus entry and Claudin-1 has been identified as a driver for liver fibrosis and hepatocellular carcinoma (HCC). Moreover, Claudins have emerged as therapeutic targets for liver disease and HCC. CLDN1 expression is upregulated in liver fibrosis and HCC. Monoclonal antibodies (mAbs) targeting Claudin-1 have completed preclinical proof-of-concept studies for treatment of liver fibrosis and HCC and are currently in clinical development for advanced liver fibrosis. Claudin-6 overexpression is associated with an HCC aggressive phenotype and treatment resistance. Claudin-6 mAbs or chimeric antigen receptor-T cells therapies are currently being clinically investigated for Claudin-6 overexpressing tumors. In conclusion, targeting Claudin proteins offers a novel clinical opportunity for the treatment of patients with advanced liver fibrosis and HCC.
Keywords: Claudins; monoclonal antibodies; therapeutic target; signaling; cell plasticity